2021
DOI: 10.3346/jkms.2021.36.e79
|View full text |Cite
|
Sign up to set email alerts
|

Performance Changes Following the Revision of Organ Allocation System of Lung Transplant: Analysis of Korean Network for Organ Sharing Data

Abstract: Background There is currently a lack of data on the impact of the recent revision of the domestic lung allocation system on transplant performance. Methods We conducted a retrospective analysis of transplant candidates and transplant patients registered in Korean Network for Organ Sharing between July 2015 and July 2019. Study periods were classified according to the introduction of the revised lung allocation system as follows: period 1 from July 2015 to June 2017 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…In the same context, other studies have shown that there was no difference in the utilization of the heart, liver, and kidney with the donor in the prone and supine positions [4,7]. The mortality on the waiting list has been high because of the imbalance between the number of available organs and potential recipients [3]. Therefore, it is necessary to increase the number of available lungs for transplantation through active lung management of marginal or unacceptable donors [8].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the same context, other studies have shown that there was no difference in the utilization of the heart, liver, and kidney with the donor in the prone and supine positions [4,7]. The mortality on the waiting list has been high because of the imbalance between the number of available organs and potential recipients [3]. Therefore, it is necessary to increase the number of available lungs for transplantation through active lung management of marginal or unacceptable donors [8].…”
Section: Discussionmentioning
confidence: 99%
“…The mortality on the waiting list has been high because of the imbalance between the number of available organs and potential recipients [ 3 ]. Therefore, it is necessary to increase the number of available lungs for transplantation through active lung management of marginal or unacceptable donors [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since then, efforts have been made to distribute and manage organs fairly and efficiently according to the Internal Organs Transplant Act [ 5 ]. The current donor lung allocation system is based mainly on urgency, with additional points allocated according to region, blood type, wait time, previous donation history, and age [ 6 ]. Transplant candidates are classified as 0–4 according to urgency; a lower status indicates a higher priority.…”
Section: Current Korean Lung Allocation Systemmentioning
confidence: 99%